A case of pituitary stalk interruption syndrome diagnosed in a 2-year-old child masquerading as syndrome of inappropriate antidiuretic hormone secretion - Kumble, Ali; Phadke, Abhishek K.; Nazar, Sapheliya (International Journal of Scientific Reports, 2021)
Pituitary stalk interruption syndrome (PSIS) is included under the spectrum of midline abnormalities and is considered as a part of the holoprosencephaly (HPE) wide spectrum. Genetic basis has been identified in few familial cases. PSIS have anterior pituitary hormone deficiencies and a wide spectrum of clinical presentation. The typical clinical manifestations of PSIS are growth retardation, hypoglycemia and delayed puberty. We report a case of PSIS with hyponatremic seizures as initial presentation. Two-year-old girl with growth and development appropriate for age, presented with acute respiratory infection and generalized tonic clonic seizures. There was history of similar illness two weeks prior and was treated for hyponatremia. Child had euvolemic hyponatremia and symptomatic hypoglycemia. Serum cortisol level was observed to be low and thyroid function test was abnormal. MRI brain showed hypoplastic anterior pituitary and ectopic posterior pituitary (hallmark of PSIS) and absent septum pellucidum. Child was treated with hormone replacement therapy with hydrocortisone and thyroxine. Child improved and is on follow up. Clinical suspicion, early diagnosis and treatment prevent worsening of endocrine impairment, permanent short stature and associated morbidities with PSIS.